Prioritizing agri-food system investments under climatic and world price risks - Aragie, Emerta A. (International Food Policy Research Institute, 2024)
With a population exceeding 120 million, Ethiopia is home to 77 million people who directly depend on agriculture for their livelihoods (World Bank, 2024a). The country registered robust agricultural growth of about 5% on average for a decade since 2013 (NBE, 2023). The Ethiopian government has been encouraged to target its development interventions to sustain and accelerate the growth and transformation of the economy (IFAD, 2023; Aragie & Balié, 2019). However, the pattern of support and the composition of growth are critical factors influencing changes in poverty, employment, and diet quality (Christiaensen & Martin, 2018; Pham & Riedel, 2019). Assessing the linkages between economic growth and poverty, employment, and diet quality is a topic of importance to both country policymakers and their development partners. Few studies, including Fan and Zhang (2008), Aragie, et al (2022), Benfica, et al. (2019) and Pauw and Thurlow (2015), have so far assessed and ranked various on-farm and off-farm interventions in relation to their impacts on selected outcome indicators and suggested to policy makers the most cost-effective ways of allocating scarce public resources for maximum impact.